2020
DOI: 10.33448/rsd-v9i2.2197
|View full text |Cite
|
Sign up to set email alerts
|

Evolução da leishmaniose visceral em São Luís, Maranhão: uma análise epidemiológica e temporal dos casos

Abstract: Visceral Leishmaniasis (VL), popularly known as kala-azar, dundun fever or tropical splenomegaly, is a zoonosis that affects humans and other domestic and wild animal species. The present work aims to carry out an epidemiological analysis from 2008 to 2017 of visceral leishmaniasis in the city of São Luís–MA. A retrospective, descriptive and quantitative study was carried out on the confirmed cases of visceral leishmaniasis reported in the municipality of São Luís, capital of Maranhão state, between 2008 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
1
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
6
1
1
3
Order By: Relevance
“…These findings were similar to those described by Cavalcante and Vale (2014) and Sousa et al (2020) who also reported high percentages data classified as "not applicable" (Sousa et al, 2020;Cavalcante & Vale, 2014). This finding may be associated with the fact that patients under 5 years of age, who do not yet attend elementary school and that this age group corresponds to 35.51% of the cases affected by AVL (Sousa et al, 2020;Alves & Fonseca, 2018). This education profile has been reported previously and helps to explain the importance of education related to health and prevention of infectious and parasitic diseases, especially in endemic areas, since our results also showed that individuals with low education comprised the majority of patients (Alves & Fonseca, 2018;Sousa et al, 2018;Barbosa et al, 2013).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These findings were similar to those described by Cavalcante and Vale (2014) and Sousa et al (2020) who also reported high percentages data classified as "not applicable" (Sousa et al, 2020;Cavalcante & Vale, 2014). This finding may be associated with the fact that patients under 5 years of age, who do not yet attend elementary school and that this age group corresponds to 35.51% of the cases affected by AVL (Sousa et al, 2020;Alves & Fonseca, 2018). This education profile has been reported previously and helps to explain the importance of education related to health and prevention of infectious and parasitic diseases, especially in endemic areas, since our results also showed that individuals with low education comprised the majority of patients (Alves & Fonseca, 2018;Sousa et al, 2018;Barbosa et al, 2013).…”
Section: Resultssupporting
confidence: 92%
“…Regarding evolution, we observed a high cure rate and low number of deaths when patients received adequate treatment for AVL. Results like ours have been described in other regions (Sousa et al, 2020;Santos et al, 2018;Santos et al, 2017). Higher death rates than those in our study were reported in the city of Bauru (SP), in which 8.1% of individuals died (Ortiz and Anversa, 2015).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…, a taxa de letalidade foi de 9,7% e com o estudo de Silveira e Oliveira (2020), no Development, v. 9, n. 11, e489119170, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9170 Maranhão de 2007-2017, os óbitos por LV foram 366, letalidade de 5,99%, o Piauí não tem uma letalidade tão alta. Mesmo a letalidade por LV encontrada no Piauí não está elevada, há a necessidade de medidas de controle para diminuir a letalidade por essa doença no Piauí, pois o Ministério da Saúde apregoa que a taxa de letalidade deve ser inferior a 5%.…”
Section: Variáveisunclassified
“…Considerando os dados analisados é possível identificar um aumento da infecção de Leishmaniose visceral/ HIV o qual é retratado na Figura 2 que entre os anos de 2010 a 2017 houve um aumento de 14,64% de infectados, apesar dos anos de 2014 a 2015 houve uma pequena queda de 4% com tendência a uma estabilidade depois. É registra do o ano de 2017 e 2018 com o maior número de casos com Leishmaniose visceral/HIV em São Luis do Maranhão que foi de 17,13%(n=55), esse aumento está diretamente relacionado com a intensa e rápida urbanização pela qual a cidade tem vivenciado nos últimos anos o qual acabou provocando uma migração de doenças que eram típicas do meio rural para as cidades de pequeno e médio porte o qual tornou um problema de saúde pública(Pantoja et al, 2020;Sousa et al, 2020).Sabe-se que, via de regra, a LV atinge, preferencialmente, a população infantil. Entretanto, verifica-se uma tendência para a diminuição do número de casos em crianças e o aumento da infecção em adultos, principalmente devido à associação com o HIV(Barbosa et al,2013).…”
unclassified